Anesthesia Management of Patients with Esophageal Atresia/Traceoesophageal Fistula undergoing Thoracostomy and Esophagostomy Procedures - Marthendro, Triade; Irawan, Dino; Muharrami, Vera; Hidayat, Nopian; Ananda, Pratama (Journal La Medihealtico, 2024)
Esophageal atresia is a congenital disorder characterized by a disruption in the continuity of the esophageal lumen. Esophageal atresia may be accompanied by tracheoesophageal fistula, which is a lumen connection between the proximal and or distal part of the esophagus and the airway (trachea). Type C atresia is the most prevalent, which is approximately 88.5% to 90% of cases, where there is proximal esophageal atresia with distal tracheoesophageal fistula. In this case, a 9-day-old infant was admitted to Arifin Ahmad Hospital for thoracostomy and esophagostomy surgery due to continuous mucus discharge. The patient underwent awake intubation and was positioned intraoperatively, with a tilt to the right when an orogastric tube was placed. During surgery, the patient maintained stable hemodynamic and was subsequently admitted to the NICU using a ventilator. Infants with esophageal atresia often show symptoms of hypersalivation and shortness of breath caused by aspiration pneumonia. When the nasogastric tube cannot pass through the esophagus, atresia can be suspected. Radiology studies play an important role in diagnosing esophageal atresia, confirming esophageal atresia with or without fistula and diagnosing other anomalies associated with VACTERL.